IMPLEMENTASI METODE FUZZY ANALYTICAL HIERARCHY PROCESS (F-AHP) DALAM PENENTUAN PRODUK SAMPINGAN KOPI (STUDI KASUS UMKM TEMU HURIP) - Kurniawan, - (2019)
In the era of globalization and high competition, making UMKM Temu Hurip must be able to increase product and service innovation. In order to reduce the residue from the production process, UMKM Temu Hurip make use of being a byproduct that has a high selling price after the main coffee product. The purpose of this research is to determine the best alternative byproduct using the Fuzzy Analytical Hierarchy Process method. Data collection is obtained from the results of discussions and interviews with several stakeholders. There are 3 criteria, 7 subcriteria and 3 alternatives that is organic fertilizer, animal feed and tea. In the assessment process of each criterion, subcriteria and alternatives only use 1 expert. Data processing uses the AHP method to test the consistency of the data that has been taken so that it can proceed to the Fuzzy. The next step is to use the Fuzzy AHP method because it can eliminate the value of subjectivity and then look for the highest priority of the by-product. From this research the highest priority was chosen as a by-product, specifically Tea with 83% weight followed by Organic Fertilizer (0.14) and Animal Feed (0.03)